Protoporphyrin IX accumulation disrupts mitochondrial dynamics and function in ABCG2‐deficient hepatocytes. Issue 19 (14th August 2013) - Lin, Yu-Hsing; Chang, Hsiao-Min; Chang, Fang-Pei; Shen, Chia-Rui; Liu, Chao-Lin; Mao, Wan-Yu; Lin, Chung-Chih; Lee, Hsuan-Shu; Shen, Chia-Ning
Abstract : Targeted inhibition of multidrug ABCG2 transporter is believed to improve cancer therapeutics. However, the consequences of ABCG2 inhibition have not been systematically evaluated since ABCG2 is expressed in several organs including the liver. Here, we demonstrate that ABCG2‐deficient hepatocytes have increased amounts of fragmental mitochondria accompanied by disruption of mitochondrial dynamics and functions. This disruption was due to ABCG2 knockout elevating intracellular protoporphyrin IX, which led to upregulation of DRP‐1‐mediated mitochondrial fission. The finding that ABCG2 deficiency can generate dysfunctional mitochondria in hepatocytes raises concerns regarding the systematic use of ABCG2 inhibitor in cancer patients. Abstract : Reduction in glycogen storage in the liver of ABCG2 knockout mice. Increase in fragmental mitochondria in ABCG2‐deficient hepatocytes. ABCG2 knockout leads to impairment in mitochondrial dynamics and function. Efflux of excessive PPIX is mediated by the ABCG2 transporter in mouse hepatocytes. PPIX accumulation induces DRP‐1‐mediated mitochondrial fission.